ADDITIONS TO FOSSIL FISHES OF MEXICO IN ELASMOBRANCHS - MALDONADO KOERDELL, MANUEL (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1935)
Gonopodial characters of Priapella and descr of a paratypic male of P bonita are given P compressa, descr from Palenque, Chiapas, differs from P bonita in the greater head length and greater depth of body Females of P compressa have longer depress
REV SOC MEX HIST NAT
Keywords: ADDITIONS, FOSSIL FISHES, MEXICO I, ELASMOBRANCHS; CIENCIAS DE LA VIDA; PALEONTOLOGIA; PALEONTOLOGIA ANIMAL